Clinical Outcomes of a Multi-Ingredient Coriolus versicolor-Based Vaginal Gel in Greek Women with Low-Grade Cervical Lesions: The PAPILOBS-GR Real-Life Prospective Study - Georgios Michail; Alexandros Daponte; George Valasoulis; Konstantinos Dinas; Evripidis Bilirakis; Kalliopi Pappa; Konstantinos Chronopoulos; Christodoulos Akrivis; Zoi Anastasiadi; Marinos Nikolaou; Antonios Garas; Thomas Tsiantis; et al. (Cancers, 2026)
Background: Persistent human papillomavirus (HPV) can cause low- or high-grade cervical lesions, which may progress to cervical cancer. This prospective, multicenter, real-world study assessed the effectiveness, tolerability and safety of a Coriolus versicolor-based vaginal gel for the regression of HPV-related low-grade cervical lesions in routine Greek practice. Methods: PAPILOBS-GR is a multicenter, open-label, non-interventional, prospective observational, non-comparative study conducted across 45 sites in Greece. Women aged ≥18 years with ASCUS/LSIL cytology and concordant colposcopy were enrolled. Participants received Coriolus versicolor-based vaginal gel for six months. A second 6-month cycle was offered if needed. The primary endpoint was lesion regression. Secondary endpoints included HPV clearance, patient satisfaction, biopsy evolution, tolerability, and safety. Results: Of 524 enrolled patients (mean age: 34.4 ± 10.0 years; 40.5% HR-HPV), 494 (94.3%) completed the study. Overall, 75.9% achieved lesion regression (72.1% at 6 months and 34.0% at 12 months). HPV clearance occurred in 72.0% overall (68.1% at 6 months and 50.0% at 12 months). Exploratory comparisons showed generally consistent effectiveness across subgroups, including women with HR-HPV, those aged >40 years, and vaccinated participants. No significant differences in clinical endpoints were observed in association with age or vaccination status. Among 22 patients with baseline and 12-month biopsies, 59.1% showed histological improvement. Satisfaction scores exceeded 8/10 at 6- and 12-month follow-ups. Only two non-serious possibly product-related adverse events were reported. Conclusions: Coriolus versicolor-based vaginal gel was associated with high rates of lesion regression and excellent tolerability, reinforcing previous clinical findings and supporting its potential role as an adjunctive approach during watchful waiting for HPV-positive low-grade cervical lesions.